Pengendalian Suspensi Kendaraan menggunakan Pengendali Sliding Mode Control dan Proposional Integral Derivative - Ahmad Faizal; Elfira Safitri; Rudy Kurniawan (Jurusan Teknik Elektro, Universitas Bangka Belitung, 2022)
The suspension system serves to provide comfort, security, and safety for the driver and passengers while driving. The uneven road surface causes vibrations in the suspension system so that driving comfort for the driver or passenger is disrupted. For this reason, the car's suspension system should be controlled to minimize vibration. The method used in this study is to use a Sliding Mode Control (SMC) controller because the SMC controller is a feedback control with a high-speed switching system added to a Proportional Integral Derivative (PID) controller. This study aims to design an SMC controller with a combination of PID controllers on the suspension system by providing some disturbances to optimize the vibration of this system. From the results of the study, it was found that the simulation of the SMC and PID controllers was able to make the system response stable again to the initial position with the value of settling time obtained at 0.0232 seconds (0.0232s). Suspension control to minimize vibration using SMC and PID controllers can be said to have almost no overshoot of 0.6% and a relatively small steady state error of 0.00011 m.